(untitled) (Research, Society and Development, 2020)
The supply in the public sphere has always been a challenge for public administrators. Public procurement has proved to be a key factor for the functioning of any public agency. To be effective in your actions, organizational planning is need for to make good use of public resources. This article discusses how planning can contribute to optimize purchasing management at the Federal Education Institutes (IFE, the acronym in portuguese). For this, a qualitative approach is used, exploratory research, with the use of bibliographic research and documentary research to support the analyzes. The main challenges to the effective implementation of planning in acquisitions and contracts in the IFE be shown as well as reflections and strategies are proposed to improve public procurement.